Optimal taxation in the extensive model - Philippe Choné; Guy Laroque (Institute for Fiscal Studies (IFS), 2008)
We study optimal taxation in the general extensive model: the only decision of the participants in the economy is to choose between working (full time) or staying inactive. People differ in their productivities and in other features which determine their work opportunity costs. The qualitative properties of optimal tax schemes are presented, with an emphasis on the role of heterogeneity in the equity-efficiency tradeoff. When the government has a redistributive stance, there are a number of cases where the low skilled workers face larger financial incentives to work than in the laissez-faire (negative average tax rates). In particular, this occurs whenever the social weights vary continuously with income and the social weight assigned to the less skilled workers is larger than average.
Keywords: H21; H31; 330; optimal taxation; extensive model; welfare; Arbeitskräfte; Arbeitsproduktivität; Arbeitsangebot; Arbeitslosigkeit; Steuerpolitik; Wohlfahrtseffekt; Theorie